Outbreak of Puffer Fish Poisoning in Dhaka City - Islam, Mohammad Rafiqul; Chowdhury, Fazle Rabbi; Das, Sudip Kumar; Rahman, Sheikh Md Mahmudur; Amin, Md Robed (Journal of Medicine, 2017)
Background: Puffer fish poisoning is quite uncommon but not rare in Bangladesh. This is not a very common fish in Bangladesh and consumed predominantly by poor class of people as it is cheap. Puffer fishes are considered toxic because they possess a potent neurotoxin, tetrodotoxin (TTX) and its analogs. Methods: In October 2014, total 11 patients from two families got admitted in Medicine unit of Dhaka Medical College on the same day with the complaints of tingling, numbness, dizziness, vertigo, postural instability and breathlessness. Both the families admitted, have ingested Puffer fish. A case control study was done where the control were taken from the vicinity with same socioeconomic background. The control group decline of any ingestion of portion of puffer fish. Hence the results and discussion are based on meticulous observation of cases. All the cases were clinically analyzed on different variables. Results: Total 11 patients were from two families, lives half kilometer apart, from Dholaipar, Jatrabari, Dhaka. Mean age of cases were 25.18. Among eleven cases, 7 were male and 4 were female. Mean of lag period between Puffer fish intake and development symptom was 99.44 minute (SD 97.28). Mean of lag period between development of symptom and hospitalization in puffer fish intake group was 308.57 minute (SD 198.78).There were 4 deaths those didn’t receive Neostigmine and respiratory support. Total 2 patient received Neostigmineand they recovered. Neostigmine is protective in Puffer fish poisoning (RR .889 <1) but the association is not significant (95% CI on both sides of 1). Conclusion: Cluster of Puffers fish poisoning presenting as outbreaks are associated with serious consequence. The early presentation to health facility and timely neostigmine application and or respiratory support can be lifesaving. J MEDICINE Jan 2018; 19 (1) : 30-34